2022
DOI: 10.1136/bmjopen-2021-053111
|View full text |Cite
|
Sign up to set email alerts
|

RETurn to work After stroKE (RETAKE) Trial: protocol for a mixed-methods process evaluation using normalisation process theory

Abstract: ObjectivesThis mixed-method process evaluation underpinned by normalisation process theory aims to measure fidelity to the intervention, understand the social and structural context in which the intervention is delivered and identify barriers and facilitators to intervention implementation.SettingRETurn to work After stroKE (RETAKE) is a multicentre individual patient randomised controlled trial to determine whether Early Stroke Specialist Vocational Rehabilitation (ESSVR) plus usual care is a clinically and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Assessing whether interventions are delivered as planned helps trialists understand effectiveness outcomes [12] and researchers to understand implementation issues for future trials [40]. This learning has since informed fidelity assessment in other trials [26,41]. This study has indicated the most useful methods for measuring fidelity in a future trial, so that we better understand why a complex intervention works or fails [42] and improve future trial designs [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing whether interventions are delivered as planned helps trialists understand effectiveness outcomes [12] and researchers to understand implementation issues for future trials [40]. This learning has since informed fidelity assessment in other trials [26,41]. This study has indicated the most useful methods for measuring fidelity in a future trial, so that we better understand why a complex intervention works or fails [42] and improve future trial designs [43].…”
Section: Discussionmentioning
confidence: 99%
“…Fidelity was measured as part of an embedded mixed methods process evaluation [25,26] and involved multiple methods. The conceptual framework CFIF [19] was used to guide both the measurement of fidelity and understand factors affecting its delivery.…”
Section: Methodsmentioning
confidence: 99%
“…To assist future comparative evaluations of VR trials, the process evaluation protocol was planned to be similar to that within the RETAKE trial, evaluating Early Stroke Specialist Vocational Rehabilitation to enable people in returning to work [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…The initial structure of the ESSVR fidelity checklist was based on a checklist developed for an earlier VR study [ 42 ] for people with traumatic brain injury. The logic model and intervention descriptions [ 43 ] provided the initial content for the development of the ESSVR fidelity checklist.…”
Section: Methodsmentioning
confidence: 99%